Assessing nitrous oxide and nitrate leaching mitigation potential in US corn crop systems using the DNDC model. (October 2019) - Ingraham, Peter A.; Salas, William A.
Abstract: Nitrous oxide (N2 O, a potent greenhouse gas; GHG) is emitted at relatively high rates from corn-based agricultural systems. N2 O mitigation strategies, in addition to reducing GHG emissions, ideally would not increase other harmful pollutants (such as leached nitrate, NO3, or volatilized ammonia, NH3 ) or decrease crop yield. We used the Denitrification-Decomposition model (DNDC) to simulate an array of single and combined interventions to corn management across broad range of physical conditions (climate and soil) in the Midwest US. We assumed a typical crop management baseline of continuous corn or corn-soy with conventional tillage and urea-ammonium nitrate fertilizer broadcast to the soil surface. Interventions included fertilizer nitrogen (N) form, controlled-release N, addition of nitrification inhibitors, N rate, split sidedress N applications, sub-soil N placement, and reduced tillage. Single-factor interventions which reduced N2 O in all locales included a change to urea fertilizer, nitrification inhibitors, reductions to N rate, and use of N injection: urea fertilizer and nitrification inhibitors both reduced N2 O emissions on average (30 and 9%, respectively) while simultaneously reducing NO3 leaching and mostly neutral effects to yield; N rate reductions reduced N2 O (11%) but had modest negative effects to yield. Other single-factor interventions increase N2 O emissions or N leaching on average but could have beneficial effects under some conditions. Combined interventions frequently include (>50% of the time) urea, nitrification inhibitors, and reduced N. Interventions that, even when combined with other interventions, do not reduce N2 O emissions and N leaching include anhydrous ammonia fertilizer, controlled release, and injection. Controlled-release fertilizer results were contrary to those reported in most field studies indicating that DNDC's simulation of linear N release over time may be too simplistic to replicate field conditions. Highlights: DNDC-simulated changes to N2 O and N leaching from crop management generally correspond well to similar field-measured changes Combinations of N rate reductions, nitrification inhibitors, and urea fertilizers have broad effectiveness region-wide Many single-factor interventions reduce N2 O in some areas but require site evaluation to ensure that they do not increase N2 O